ANALISIS VARIABEL PENGARUH ANTECEDENTS BAGI KEYAKINAN DIRI (SELF-EFFICACY) YANG BERPENGARUH PADA MOTIVASI PRA PELATIHAN - Martha, Lelyana Martha; Djastuti, Indi Djastuti; Yuniawan, Ahyar Yuniawan (Universitas Muhammadiyah Magelang, 2010)
Motivation to participate in training program is a personal impulse towards the situation and condition at work which influenced by three main key i.e: individual effeort, organization goal and personal needs that will determine the individual work achievement and also work performance to reach the goal. There are some related and determined variables in teachers' motivation to participate in training such as job involvement, organization commitment, work environment and self-efficacy. The goal of the thesis is to find out the intensity of the relationship between job involment, organization commitment, work environment and self-efficacy and pre training motivation. The model of this thesis has been improved based on last research done by Tracey, Hinkin, Tannenbaum and Mathieu (2001). This thesis has 212 senior high school teachers in Semarang City as samples which determined by Proportional Random Sampling methode. Beside that, it uses the SEM (Structural Equation Modeling) as the statistical analysis. The test result towards the hyphothesis shows us that the variables of job involvement, organization commitment, work environment positively affect on self-efficacy, which than continue affect on pre training motivation. Based on competing model that offered by the writer, shows that job involvement and work environment also directly affect on pre training motivation.